1986
DOI: 10.1111/j.1475-682x.1986.tb01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Bad Boys and School Suspensions: Public Policy Implications for Black Males

Abstract: The focus of this research is the disciplinary policy of school suspension and its effect on black male students. We examined the application of public school suspensions by race and sex in an integrated school district in the southeastern portion of the United States. Data for the study were compiled from oficial records housed in the administrative complex for the entire school district. The suspensions cover one academic year from September of 1983 through June of 1984. During this period of time black male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 2 publications
1
34
0
Order By: Relevance
“…In comparison to Hispanic and White girls, Black girls are more likely to be suspended from school (Raffaele Mendez et al 2002). Taylor and Foster (1986) found that Black girls received higher suspension rates than White girls in elementary, junior high, and high school, but noted declines in suspension rates from junior high school to high school for all girls. Nearly two decades later, Raffaele Mendez and Knoff (2003) replicated and extended these findings indicating that Black girls received higher suspension rates in comparison to White and Hispanic girls across primary and secondary school.…”
Section: Discipline Experiences Of Black Girlsmentioning
confidence: 95%
“…In comparison to Hispanic and White girls, Black girls are more likely to be suspended from school (Raffaele Mendez et al 2002). Taylor and Foster (1986) found that Black girls received higher suspension rates than White girls in elementary, junior high, and high school, but noted declines in suspension rates from junior high school to high school for all girls. Nearly two decades later, Raffaele Mendez and Knoff (2003) replicated and extended these findings indicating that Black girls received higher suspension rates in comparison to White and Hispanic girls across primary and secondary school.…”
Section: Discipline Experiences Of Black Girlsmentioning
confidence: 95%
“…These factors could easily intersect with other child, parent, and school factors such as pursuit of tangible rewards outside of school, meager parental supervision, and poor school climate. At a more global level, severe, system-wide attendance problems and use of suspensions in a school district can help destabilize neighborhoods, fuel gang-related activity, and contribute to malaise among teachers and other school personnel (Eitle and Eitle 2004;Taylor and Foster 1986). Criterion three: fluidity and flexibility A satisfactory model of school absenteeism must also be fluid and flexible enough to account for rapid changes in attendance patterns, symptoms, and exigent influences.…”
Section: An Interdisciplinary Model Of Problematic Absenteeismmentioning
confidence: 97%
“…The overrepresentation of African American students in suspension and expulsion practices at school has been documented consistently in the literature across time. Virtually every study undertaken of schools and school districts has revealed the same types of disparities (Costenbader and Markson, 1998;Gregory, 1997;McCarthy and Hoge, 1987;Mendez et al, 2002;Morris and Goldring, 1999;Morrison et al, 2001;Nichols et al, 1999;Skiba et al, 1997Skiba et al, , 2000Skiba et al, , 2002Taylor and Foster, 1986;Thornton and Trent, 1988;Wu et al, 1982).…”
mentioning
confidence: 93%
“…Most of the research on school punishment has focused on documenting race differences and looking for student and school-level factors to help explain disproportionality in out-of-school suspension (Costenbader and Markson, 1998;Gregory, 1997;Mendez et al, 2002;Morrison et al, 2001;Nichols et al, 1999;Skiba et al, 1997;Taylor and Foster, 1986;Wu et al, 1982). Less work has been done examining teachers and their potential effect on school suspension.…”
mentioning
confidence: 95%
See 1 more Smart Citation